Situation Report: Hungary, 2 March 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Latest Polish Visitor: Foreign Minister Stefan Olszowski / by Alfred Reisch Foreign Minister Puja in Paris / by Alfred Reisch Can the New Law Decree Solve the Problem of Alcoholism / by Judith Pataki Hungarians in Yugoslavia: A Storm in a Teacup / by Slobodan Stankovic The Woes of Hungarian Metallurgy / by Laszlo Rasko Experiments with New Method of Income Regulation / by Eva Lengyel Strong Call for Diversity within the Communist Block / by Alfred Reisch